FRAME ANALYSIS OF INSTITUTIONAL POLITICAL DISCOURSE: THE CASE OF PAKISTAN’S SPEECHES IN UNITED NATIONS GENERAL ASSEMBLY (Contemporary Journal of Social Science Review, 2025)
Leaders from all over the world use the United Nations General Assembly (UNGA) as a vital forum to discuss important global issues, state their nation's position, and have diplomatic conversations. The addresses to the UNGA are very important to Pakistan since these show the nation's foreign policy priorities and how it has responded to regional and international issues. The study entails the frame analysis of speeches produced in UNGA sessions. This study examines the frames and their framing functions in speeches given to the United Nations General Assembly (UNGA) by different well-known Pakistani leaders. For this purpose, five speeches from the year 2020 to 2024 are selected as the study sample using the purposive sampling method. The research follows qualitative approach and content analysis method is used to interpret the data. Frame analysis method proposed by Boydstun, et al., (2014) and Entman (2004; 2008) is used as the theoretical framework. The findings of the study show that all the framing functions are not usually found in the composition of a single frame. However, it is found that security & defense frames perform the function of problem definition; law, order, crime & justice frames focus on causal interpretation; morality frame is used to make moral evaluation and finally, policy prescription and evaluation frames propose treatment recommendations for the solution of problem.